Nano-Zagreb Index and Multiplicative Nano-Zagreb Index of Some Graph Operations - Akbar Jahanbani; Hajar Shooshtary (LPPM Institut Teknologi Sepuluh Nopember, 2019)
Let G be a graph with vertex set V(G) and edge set E(G). The Nano-Zagreb and multiplicative Nano-Zagreb indices of G are NZ(G) = _uv E(G) (d^2(u) - d^2(v)) and N*Z(G) = _uv E(G) (d^2(u) - d^2(v)), respectively, where d(v) is the degree of the vertex v. In this paper, we define two types of Zagreb indices based on degrees of vertices. Also the Nano-Zagreb index and multiplicative Nano-Zagreb index of the Cartesian product, symmetric difference, composition and disjunction of graphs are computed.